THE INFLUENCE OF MARKETING MIX STRATEGY ON STUDENTS' DECISION TO CHOOSE PLJ KAMPUS TANGERANG SELATAN (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to determine the extent of the influence of the Marketing Mix Strategy on students' decisions to choose the PLJ Kampus Tangerang Selatan. The research employs a quantitative approach using a survey method. The population consists of 92 active students from PLJ Kampus Tangerang Selatan (Levels I, II, and III) who enrolled during the 2023/2024, 2024/2025, and 2025/2026 academic years. The sample size for this study is 75 active students. Simple linear regression analysis yielded the equation Y = 3.238 + 0.132X, indicating that in the absence of a marketing mix strategy, the purchasing decision value is 3.238. Hypothesis testing results demonstrate the significance of the marketing mix strategy regarding the purchasing decision, with a significance value (Sig.) of 0.000 < 0.05 (leading to the rejection of Ho and acceptance of Ha) and a calculated t-value of 12.648 exceeding the t-table value of 1.993. This implies that the Marketing Mix Strategy has a positive and significant influence on the Purchasing Decision. The Coefficient of Determination (R-Square) is 0.687, indicating that the Marketing Mix Strategy (X) explains 68.7% of the Purchasing Decision (Y), while the remaining 31.3% is influenced by other variables not examined in this study.